THE IDEOLOGY BEHIND THE EFFORTS TO DESIGNATE THE HOUSE OF THE NYOMAN RAI SRIMBEN AS A CULTURAL RESERVE - I Wayan Eka Wiranata; Ni Ketut Puji Astiti Laksmi; Ida Ayu Laksmita Sari (E-Journal of Cultural Studies)
Cultural reserve is something that must be preserved as it holds important values, including history, science, education, religion, and culture. The house of Nyoman Rai Srimben, where a woman gave birth to Ir. Soekarno, Indonesia's first president, represents these core values. In 2022, the Bali Provincial Cultural Service recommended that Nyoman Rai Srimben’s house be designated as a provincial cultural reserve site. Reflecting on the background, this research paper aims to achieve three main objectives. First, it will analyse the factors that motivated the Bali Provincial Cultural Service to designate the house as a cultural reserve site. Second, it will examine the underlying ideology behind this designation. Third, it will explore the implications of the designation. This research is qualitative study, using data collection methods such as observation, interviews, and document analysis. The theories used in this paper are the theory of power/knowledge relations and the theory of hegemony. A deductive approach is employed in the data analysis. The findings reveal that the Bali Provincial Cultural Service’s decision to designate the house as a cultural reserve site is based on two key factors: (1) an internal factor, originating from the community that owns the property who possess the historical knowledge; and (2) an external factor, related to the enforcement of Law No. 11 of 2010 concerning reserve. The final result focuses on the implications of the designation, which has led to shifts in the cultural, economic, and social aspects related to the house of Nyoman Rai Srimben. These shifts include changes in the protection, development, and utilization of the site.